G64 An exploration of attitudes towards female genital mutilation/cutting (fgm/c) in men and women accessing fgm/c services. (24th May 2017) - Larsson, M; Cohen, P; Creighton, SM; Hodes, D; Hann, G
Abstract : Aims: It is estimated that 1 37 000 females in the UK are affected by female genital mutilation/cutting (FGM/C), of which 10 000 are under 15 years old. This pilot cross-sectional study aimed to address the knowledge gap in the UK regarding attitudes towards the continuation of FGM/C: an important child protection and legal issue. The primary objective was to measure the proportion of adults who report that they believe FGM/C should stop. Secondary objectives included assessing knowledge of the FGM/C UK law and health risks. Methods: The participant population consisted of English-speaking adults accessing specialist FGM/C services at two hospitals. Eligible women and accompanying partners were approached. Those who consented to participate were given an information sheet, consent form and questionnaire to complete in a private room in the clinic. Results: 54 (51 women, three men) from 90 eligible participants asked, participated. 96% (49/51) of the women reported they had undergone FGM/C, with half aged between five and ten at the time. 33% of participants did not know which FGM/C type they had, and 31% said they were 'cut, with some flesh removed'. 89% (48/54) of participants reported they thought FGM/C should stop (95% CI: 0.81 to 0.97), and none stated that FGM/C should continue. 72% (39/54) knew FGM/C was illegal in the UK with 22% not knowing and 6% of answers missing. Four participants reported that FGM/C caused no danger to women's health. Conclusion: The results demonstrate most opposed FGM/C in this sample, but illustrates the imperative for those from practicing communities to understand UK law and FGM/C-related health risks. Non-attendees may represent different viewpoints; bias is therefore likely. This pilot supports the necessity for a UKwide study regarding attitudes towards FGM/C. Our study documents could be used with minor amendments to the design, as several participants had difficulties understanding certain questions. Safeguarding children in the context of FGM/C is everybody's business. The outcomes of future research will help shape government understanding and policies, and improve prevention strategies to end FGM/C.